Tonal hierarchy representations in auditory imagery. - Vuvan, Dominique; Schmuckler, Mark (Memory & Cognition, 2011)
Two experiments investigated psychological representations of musical tonality in auditory imagery. In Experiment 1, musically trained participants heard a single tone as a perceptual cue and built an auditory image of a specified major tonality based on that cue; participants' images were then assessed using judgments of probe tones. In Experiment 2 participants imaged a minor tonality rather than a major one. Analysis of the probe tone ratings indicated that participants successfully imaged both major and minor tonal hierarchies, demonstrating that auditory imagery functions comparably to auditory perception. In addition, the strength of the major tonal image was dependent upon the pitch and tonal relations of the perceptual cue and the to-be-imaged tonality. Finally, representations of minor tonal hierarchies were less robust than those of major ones, converging with perceptual evidence that minor tonalities are less psychologically stable than major tonalities.